Symbioza mykoryzowa obcych i inwazyjnych gatunków drzew - Wilgan, Robin (Leśne Prace Badawcze, 2020)
The introduction of alien tree species has become a world wide phenomenon over the last centuries and the cultivation of these species is an economically important branch of forestry in many countries. However, the cultivation of alien plant species poses the threat of introducing potentially invasive species, both trees and its mutualistic symbionts, such as mycorrhizal fungi. Mycorrhizal fungi are obligatory symbionts and a key element in the proper development and functioning of trees. It is thought that mycorrhizal fungi may also profoundly influence the invasiveness of alien tree species worldwide, with the proper fungal species acting as a driver to make this invasion possible. Co-invasion of alien trees and its mutualistic symbionts are well-known in the case of pines and co-invading ectomycorrhizal fungi in the southern hemisphere. Invasive tree species constitute a major ecological and economic problem through intense competition and modification of local habitats leading to a decline in biodiversity and potentially threatening many rare, native and endangered species, including fungi. Despite the fundamental role that fungi have in the functioning of forests, the impact alien tree species could have on mycorrhizal fungi in native forest ecosystems has not received much attention. Understanding the relationships between mycorrhizal fungi and alien tree species can allow us to better predict and counter-act alien species invasions, which is necessary in order to maintain biodiversity and preserve native ecosystems. On top of that, climate change could threaten some European tree species and thus free ecological niches for other species, like alien, invasive or potentially invasive trees.